Correction: A facile deoxyuridine/biotin-modified molecular beacon for simultaneous detection of proteins and nucleic acids via a label-free and background-eliminated fluorescence assay. Issue 22 (23rd September 2020) - Yin, Fei; Liu, Liqi; Sun, Xia; Hou, Laiyong; Lu, Yu; Xue, Qingwang; Lin, Tong; Li, Xia; Li, Chen-zhong
Abstract : Correction for 'A facile deoxyuridine/biotin-modified molecular beacon for simultaneous detection of proteins and nucleic acids via a label-free and background-eliminated fluorescence assay' by Fei Yin, et al., Analyst, 2019, 144, 5504–5510, DOI: ; 10.1039/C9AN01016E .